Univalent Functions Associated with the Symmetric Points and Cardioid-shaped Domain Involving (p,q)-Calculus - Ahuja, Om; Bohra, Nisha; ÇETİNKAYA, ASENA; Kumar, Sushil (Kyungpook Natl Univ, Dept Mathematics, 2021)
In this paper, we introduce new classes of post-quantum or (p, q)-starlike and convex functions with respect to symmetric points associated with a cardiod-shaped domain. We obtain (p,q)-Fekete-Szego inequalities for functions in these classes. We also obtain estimates of initial (p, q)-logarithmic coefficients. In addition, we get q-Bieberbachde-Branges type inequalities for the special case of our classes when p = 1. Moreover, we also discuss some special cases of the obtained results.
Keywords: (p. q)-Fekete-Szego inequalities